Diet in the treatment of anxiety disorder (Research, Society and Development, 2022)
Introduction: Interest in the subject arose from the need to disseminate food and the benefits and harms of treatment, due to the significant increase in individuals with anxiety disorder. Thus, there is a need to seek diets that, through food and its bioactive compounds, can provide improvements in eating behavior and nutritional intake. Methodology: Descriptive, which seeks to highlight the benefits and harms of eating in anxiety disorders recorded in the national literature. Results: The research contributes to further clarification of the effects of anxiety in adult individuals. Conclusion: it was found that eating behavior can be greatly affected by emotions, since their food choices, the amounts ingested and the frequency of meals depend on several factors, one of them being emotions and not just their physiological needs and when characterizing the anxiety and its symptoms; it also emphasizes the importance of the nutritionist in prescribing food and supplements in the treatment and prevention of anxiety; pointing out the effects of eating behavior on anxiety disorder.